Food carbohydrates in the gut: structural diversity, microbial utilization, and analytical strategies - Lee, HyunJi; Song, JaeHui; Lee, Bokyung; Cha, Jaeho; Lee, Hyeyoung (Food science and biotechnology, 2024)
Carbohydrates, which are a vital dietary component, undergo digestion and gut fermentation through microbial enzymes to produce beneficial short-chain fatty acids. Certain carbohydrates selectively modulate the gut microbiota, impacting host health. Carbohydrate-active enzymes within the gut microbiota significantly contribute to carbohydrate utilization and microbial diversity. Despite their importance, the structural complexity of carbohydrates poses analytical challenges. However, recent advancements, notably, mass spectrometry, have allowed for their characterization and functional analysis. This review examines the intricate relationship between dietary carbohydrates and the gut microbiota, highlighting the crucial role of advanced analytical techniques in understanding their diversity and implications. These advancements provide valuable insights into carbohydrate bioactivity. Integrating high-throughput analysis with next-generation sequencing provides deeper insights into gut microbial interactions, potentially revealing which carbohydrate structures are beneficial for gut health.